VD_FINDINFO Jug / 2025 / 68 vom 17. Mai 2024 - VD Tribunal cantonal (2024)
BRIGANDAGE, REJET DE LA DEMANDE, PRÉSOMPTION D'INNOCENCE, CRÉDIBILITÉ, EXPULSIONDROIT PÉNAL | 140 CP, 46 al. 1 CP, 47 CP, 66a CP, 10 CPP (CH), 389 CPP (CH), 6 CPP (CH)